Reflections and perspectives on parental involvement in children’s school activity - Popa, Eleonora Mihaela (Technium Social Sciences Journal, 2022)
This paper aims to look at the family as a living, unique organism that evolves, transforms, and adapts according to certain conditions. With the birth of children come challenges and responsibilities that each family understands and directs differently. Assuming the parental role, translating it into desirable behaviors, family relationships, and identifying the parents' attitude towards education in general are prerequisites of how they will get involved in their child's school activities. Research results have shown that the more and more effective parents are involved, the better their children's cognitive development, academic achievement, and self-confidence increase. On the other hand, children in families with poor parental relationships will experience lower academic achievement and less confidence in their ability to cope with school tasks. Differences have also been reported between the involvement of mothers and fathers respectively, as well as some of the effects of parental absence on children.